Unlocking the Potential: Assessing the Influence of Electronic Human Resource Management on Innovative Performance, Productivity, and Cost Efficiency with Employee Satisfaction as a Key Mediator - Faiz Ahmed; Hamza Hakim; Aqil Shakoor; Qassia Shoaib (JISR Management and Social Sciences & Economics)
In recent years, human resources (HR) have taken on a new face with the advent of electronic human resource management, or e-HRM. The emergence of this new face of HR is a result of intranet and internet technology. This study aimed to investigate the function of E-HRM in Pakistan and if it has a major impact on HRM productivity, innovation performance, and cost efficiency, given the significance of HRM in a company's competitive advantage. 205 respondents in all provided complete answers, which were used for analysis. The effect of e-HRM activities (e-recruitment, e-training, e-compensation, e-communication, and e-performance appraisal) on employee satisfaction was examined using the multiple linear regression method. The impact of employee satisfaction on HRM performance (productivity, innovation performance, and cost efficiency) was also examined using this method. The study's findings showed that information technology improves employee satisfaction, which in turn boosts productivity in HRM, performance in innovation, and cost effectiveness. The findings of this study may also help managers in various organizations focus on the elements that can increase employee motivation and satisfaction level. It can assist the organization in achieving its objective, which may be improved organizational performance.